2017
DOI: 10.21276/bpr.2017.7.2.4
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Activity of Methanolic Leaf Extract of Morinda Tinctoria Roxb. Against Ehrlich Ascites Carcinoma in Mice

Abstract: The methanol extract of the leaves of Morinda tinctoria Roxb. (MEMT) was studied for its anticancer activity using in vitro and in vivo cancer models. MEMT was investigated for its short-term cytotoxicity on EAC tumor cells by trypan blue dye exclusion method and in vitro cytotoxicity on NIH 3T3, A549, Hep2 and HepG2 cells by MTT assay. In vivo anticancer activity was studied on EAC tumor-bearing mice. Anticancer activity was assessed by monitoring the mean survival time, the percentage increase in life span, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
(18 reference statements)
1
1
0
Order By: Relevance
“…This study showed that treatment with costus extract can decrease elevated EST-induced cardiac enzyme (LDH, CK, and CK-MB) levels. This result agrees with reports that EST (Aldubayan et al, 2019) and EAC (Noureldeen et al, 2017) induce increases in cardiac enzyme levels, and that methanol extract of costus has cardioprotective potential against carbon tetrachloride-induced cardiac toxicity (Njoku et al, 2017). In the current study, a significant increase in serum ALP and AST levels was observed, indicating liver and cardiac toxicity.…”
Section: Discussionsupporting
confidence: 93%
“…This study showed that treatment with costus extract can decrease elevated EST-induced cardiac enzyme (LDH, CK, and CK-MB) levels. This result agrees with reports that EST (Aldubayan et al, 2019) and EAC (Noureldeen et al, 2017) induce increases in cardiac enzyme levels, and that methanol extract of costus has cardioprotective potential against carbon tetrachloride-induced cardiac toxicity (Njoku et al, 2017). In the current study, a significant increase in serum ALP and AST levels was observed, indicating liver and cardiac toxicity.…”
Section: Discussionsupporting
confidence: 93%
“…The studies revealed that the various phytochemicals especially, terpenoids play an important role in preventing activity against the proliferation of breast cancer cells and suppressing of in vitro proliferation process. [10][11][12][13][14] Terpenoids are one of the largest classes of secondary metabolites obtained from natural resources and are structurally composed of isoprenoid units. Terpenoids are classified into six classes, including monoterpenes, sesquiterpenes, diterpenes, triterpenes, tetraterpenes, and polyterpenes, based on their structural characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer treatment and diabetes may also make a person more suffer to fungal infections (Johnson, 2018). Literature is enriched with several reports which prove plants as a potential source of bioactive secondary metabolites (Shrestha et al 2016;Dahiya et al 2019;Dahiya and Singh, 2017a;2017b;Viana et al 2017;Senthil Kumar et al 2017). Azadirachta indica, commonly known as neem and nimtree, belongs to the family Meliaceae (Figure 1a).…”
Section: Introductionmentioning
confidence: 99%